The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1046/j.1471-4159.1996.67031252.x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 Is Another Gap Junction Protein in the Peripheral Nervous System

Abstract: That many cells express more than one connexin (Cx) led us to examine whether Cxs other than Cx32 are expressed in the PNS. In addition to Cx32 mRNA, Cx43 and Cx26 mRNAs were detected in rat sciatic nerve by northern blot analysis. Cx43 mRNA, but not Cx26 mRNA, was expressed in both the primary Schwann cell culture and immortalized Schwann cell line (T93). The steady-state levels of the Cx43 mRNA in the primary Schwann cell culture increased 2.0-fold with 100 p.M forskolin, whereas that of P 0 increased 7.0-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…As precedent, protein constituents of gap junctions ("connexins") are well documented in peripheral nerve Schwann cells (Bergoffen et al, 1993;Scherer et al, 1995;Yoshimura et al, 1996;Chandross et al, 1996;Mambetisaeva et al, 1999;Nagaoka et al, 1999;Zhao et al, 1999;Altevogt et al, 2002;Li et al, 2002). Immunocytochemical evidence is strong for connexin32 (Cx32) in paranodes, at Schmidt-Lanterman incisures, and along the "inner mesaxon" of the myelin sheath (Bergoffen et al, 1993;Scherer et al, 1995Scherer et al, , 1998Spray and Dermietzel, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…As precedent, protein constituents of gap junctions ("connexins") are well documented in peripheral nerve Schwann cells (Bergoffen et al, 1993;Scherer et al, 1995;Yoshimura et al, 1996;Chandross et al, 1996;Mambetisaeva et al, 1999;Nagaoka et al, 1999;Zhao et al, 1999;Altevogt et al, 2002;Li et al, 2002). Immunocytochemical evidence is strong for connexin32 (Cx32) in paranodes, at Schmidt-Lanterman incisures, and along the "inner mesaxon" of the myelin sheath (Bergoffen et al, 1993;Scherer et al, 1995Scherer et al, , 1998Spray and Dermietzel, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Presently, at least 20 connexin proteins have been identified and characterized in rodents (Bruzzon, 2001). Changes in the expression of various gap junction gene products including connexin (Cx) 26, Cx43, and Cx46 were observed during peripheral nerve recovery, following peripheral nerve injury (Yoshimura et al, 1996;Chandross et al, 1996). Colleagues reported that gap junction proteins Cx26, Cx32, and Cx43 were differentially regulated after crush injury and that occludin frequently coexisted with Cx43 in the perineurium, suggesting that the regulation of tight junction and gap junction were closely related (Nagaoka et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of this radial pathway may be the reason that mutations in Cx32 cause X-linked Charcot-Marie-Tooth disease (CMTX), an inherited demyelinating neuropathy (Bergoffen et al 1993). Because the pathway and the rate of 5,6-carboxyfluorescein diffusion in cx32-null mice did not appear to be different than in wild-type mice (Balice-Gordon et al 1998), there appear to be functional gap junctions in the myelin sheaths formed by another connexin(s), perhaps Cx26 and/or Cx43 (Mambetisaeva et al 1999;Nagaoka et al 1999;Yoshimura et al 1996;Zhao and Spray 1998). The exis-5 Fig.…”
Section: Introductionmentioning
confidence: 99%